2022
DOI: 10.1159/000525282
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Estimates of Incidence and Prevalence of Narcolepsy: A Systematic Review and Meta-Regression Analysis

Abstract: Introduction: Narcolepsy is a chronic neurological disorder. The diagnostic criteria of narcolepsy evolve from clinical symptoms to molecular biomarkers, along with the understanding of its clinical nature and pathogenesis. Estimates of incidence and prevalence of narcolepsy vary between studies, while the contribution of changing diagnostic criteria to the variation remains unclear. We aimed to explore sources of heterogeneity in estimates of incidence and prevalence, with a particular focus on diagnostic cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The accuracy of narcolepsy prevalence estimates can be affected not only by the type of sample used, but also by differences in diagnostic criteria, potentially resulting in overestimation. A meta-regression analysis by Wang et al [ 13 ] revealed that having stringent diagnostic criteria are essential to determine the true prevalence of narcolepsy, while the use of non-specific criteria can lead to overestimates.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of narcolepsy prevalence estimates can be affected not only by the type of sample used, but also by differences in diagnostic criteria, potentially resulting in overestimation. A meta-regression analysis by Wang et al [ 13 ] revealed that having stringent diagnostic criteria are essential to determine the true prevalence of narcolepsy, while the use of non-specific criteria can lead to overestimates.…”
Section: Introductionmentioning
confidence: 99%